Electrospun polymeric nanofibers encapsulated with nanostructured materials and their applications: A review - Panthi, Gopal; Park, Mira; Kim, Hak-Yong; Park, Soo-Jin (Journal of industrial and engineering chemistry (Seoul, Korea), 2015)
Use of nanostructured materials in powder form for various applications might show excellent performances, however they create serious problem due to separation difficulty, loss and photocorrosion during use, and their reusability in the case of large scale processes. This review presents the research that has been focused on the fabrication of composite NFs in which nanostructured materials are encapsulated in polymeric matrix by means of simple, effective, low cost, high yield technique; electrospinning in order to overcome the afore mentioned problems. Polymer NFs not only act as supporter but also prevent the aggregation and leaching of nanostructures improving their performances.